Early Congenital Syphilis Presenting With A Rare Case Manifestation And Various Comorbidities: A Case Report - I Made Putra Wira Negara; Anak Agung Ayu Windi Antari; N. Wisnu Sutarja (Green Publisher Indonesia, 2024)
Congenital syphilis (CS) cases in worldwide have reached 700.000 cases until 2023. Especially late or untreated cases can cause up to 80% of poor pregnancy outcomes. This case report discusses the treatment strategy of symptomatic CS case in a newborn with multiple comorbidities. A newborn female infant was admitted with cutaneous lesions comprising white patches with a bluish-red base, as well as jaundice. The patient was born to a single mother with a history of multiple partners and never had an antenatal care. The patient exhibited pale yellow stools with a putty-like consistency and dark-yellow urine. The patient was tachypnea (oxygen saturation of 86% on room air), exhibiting jaundice of the eyes and skin (Cramer IV). Laboratory results were positive for syphilis, severe thrombocytopenia (10×103/µL), hyperbilirubinemia with total bilirubin 18.89 mg/dL, direct bilirubin 11.81 mg/dL, and indirect bilirubin 7.08 mg/dL. Babygram suggested pneumonia, while 2-phase abdominal ultrasound showed impaired gallbladder contractility. The patient was diagnosed with CS, pneumonia neonatal, and cholestasis suspicious for biliary atresia. The patient was stabilized hemodynamically, administered intravenous fluids containing dextrose 10%, benzathine penicillin G 130,000 IU was administered intramuscularly every 24 hours (10 days) according to hospital availability for syphilis treatment, combination of cefoperazone-sulbactam and gentamicin for the treatment of pneumonia, and ursodeoxycholic-acid (UDCA) for the treatment of cholestasis. The patient's condition showed gradual improvement, with the skin lesions also demonstrating improvement, although jaundice persisted. In the last follow-up, due to stable condition, the patient was discharged to outpatient with continued oral UDCA therapy.